2022
DOI: 10.1007/s40263-022-00937-x
|View full text |Cite|
|
Sign up to set email alerts
|

Antiseizure Drugs and Movement Disorders

Abstract: The relationship between antiseizure drugs and movement disorders is complex and not adequately reviewed so far. Antiseizure drugs as a treatment for tremor and other entities such as myoclonus and restless leg syndrome is the most common scenario, although the scientific evidence supporting their use is variable. However, antiseizure drugs also represent a potential cause of iatrogenic movement disorders, with parkinsonism and tremor the most common disorders. Many other antiseizure drug-induced movement diso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 203 publications
1
8
0
Order By: Relevance
“…pine, rufinamide, diazepam, primidone, felbamate, stiripentol, tiagabine and phenobarbital-had a lower probability of relating MDs. Our classification is consistent with earlier reports4,30,31 ; we all agree that ASMs such as lamotrigine, carbamazepine and valproate cause MDs, while ASMs such as clonazepam, zonisamide and gabapentin do not. In addition, the present study found pregabalin and topiramate to cause There are some drawbacks in our study that should be taken into consideration.…”
supporting
confidence: 92%
See 1 more Smart Citation
“…pine, rufinamide, diazepam, primidone, felbamate, stiripentol, tiagabine and phenobarbital-had a lower probability of relating MDs. Our classification is consistent with earlier reports4,30,31 ; we all agree that ASMs such as lamotrigine, carbamazepine and valproate cause MDs, while ASMs such as clonazepam, zonisamide and gabapentin do not. In addition, the present study found pregabalin and topiramate to cause There are some drawbacks in our study that should be taken into consideration.…”
supporting
confidence: 92%
“…3 By contrast, some researchers believed that ASMs, rather than epilepsy itself, may directly increase the risk of developing idiopathic MDs. 4 They used a case-control study approach to compare the Parkinson disease and control groups in the UK Biobank database, and found that ASMs (valproate, lamotrigine, carbamazepine and levetiracetam) were associated with an 80% increased risk of developing Parkinson disease. 5 A postmarketing study based on the Italian spontaneous reporting system showed that 6.6% of children with ASMs developed MDs.…”
mentioning
confidence: 99%
“…Sáenz-Farret et al, reviewed the literature on movement disorders secondary to antiseizure medications. They found one manuscript of CNZ-induced tremor [ 119 ]. In a randomized controlled trial of adjunctive CNB in patients with uncontrolled focal seizures, tremor was reported by seven (6.2%) CNB users and by three (2.8%) individuals in the placebo group.…”
Section: Discussionmentioning
confidence: 99%
“…In rare cases, parkinsonism cases were also reported in patients treated with lamotrigine [ 12 ]. No parkinsonism cases have yet been reported among patients treated with levetiracetam [ 13 ]. Indeed, this drug can also be used for the management of levodopa-induced dyskinesias in patients with Parkinson’s disease [ 14 ].…”
Section: Discussionmentioning
confidence: 99%